Risiko Keamanan dan Kerentanan Jaringan Transmisi Listrik Terhadap Serangan Siber pada Infrastruktur Energi Terdistribusi - Didik Aribowo; Jahra Damayanti; Muhamad Sadewa; Syafa Raihanun Nabila; Sarnata, Sarnata (Fakultas Teknik UMRI, 2024)
Cybersecurity is a major challenge for energy infrastructure in remote areas that rely on distributed power grids. Limited resources and lower levels of monitoring compared to urban areas increase vulnerability to cyberattacks. This study analyzes the key risks faced by power transmission networks in remote areas, including restricted physical access, the use of outdated and vulnerable protocols, and insufficient network segmentation. To address these challenges, this research recommends a layered mitigation strategy, including data encryption, multi-factor authentication, network segmentation, and the adoption of blockchain technology. Additionally, training local staff and regularly updating software are crucial steps in enhancing network security. This study employs a literature review method, gathering and analyzing information from various sources such as books, journals, articles, and previous research findings. Data processing is conducted systematically to identify challenges and applicable solutions to improve the reliability of energy infrastructure in remote areas. The implementation of these recommended strategies is expected to reduce cybersecurity risks and enhance the security of power grids in such regions.